Self‐report instruments for measuring patient dignity: A psychometric systematic review. (7th September 2022) - Lam, Le Trinh; Chang, Hsin‐Yi; Natashia, Dhea; Lai, Wei‐Shu; Yen, Miaofen
Abstract: Aims: To synthesize and evaluate the psychometric properties of self‐report instruments that measure patient dignity. Design: A psychometric systematic review. Data sources: A comprehensive search of studies published from inception until February 17, 2022, was performed using PubMed, Embase, CINAHL, Web of Science, and Scopus. Review Methods: The methodological quality of the psychometric studies was evaluated following the COnsensus‐based Standards for the selection of health Measurement INstruments (COSMIN) guidelines. Results: Eleven self‐report instruments that evaluate dignity were identified. For most instruments, psychometric properties, including reliability, cross‐cultural validity, responsiveness, and measurement error, had not been adequately examined. The Patient Dignity Inventory (PDI), the Jacelon's Attributed Dignity Scale (JADS), and the Inpatient Dignity Scale (IPDS) had acceptable content validity, structure validity, and internal consistency to measure dignity among adult patients under palliative care, community‐dwelling older adults, and inpatients receiving daily care. Conclusion: The PDI, the JADS, and the IPDS are recommended for future clinical practice and research to measure dignity among adult patients under palliative care, community‐dwelling older adults, and inpatients receiving daily care. Early identification of patients' dignity‐related problems in nursing care can prevent negative health outcomes and help develop a timely intervention to promote patients' health and recovery. Impact: Given that the psychometric properties of the existing self‐report dignity instruments have not been systematically assessed, the present review utilized comprehensive methods according to COSMIN to evaluate and determine the most appropriate measure for research and practice. The PDI, the JADS, and the IPDS demonstrated satisfactory psychometric properties and are, thus, recommended for clinical and research applications. Nursing professionals can employ these instruments to assess and promptly identify dignity issues among both young and older adults in hospitals and communities.